Analisis Resiliensi Penghidupan Petani Padi Penerima Hibah Sibedas di Kabupaten Bandung Menggunakan Kerangka Sustainable Livelihood Approaach (SLA) - Yuhasyra, Dzikra; Karyani, Tuti; Dwiartama, Angga (Universitas Galuh, 2025)
Agriculture plays a crucial role in the economy of Bandung Regency, particularly in Ciparay and Rancaekek Districts. However, challenges such as land conversion, climate change, and market fluctuations affect agricultural productivity and sustainability. In response, the Bandung Regency Government implemented the Sibedas Farmer Card Program, aimed at improving farmers' welfare through input subsidies and access to agricultural insurance. This study examines the relationship between the Sibedas Farmer Card policy, livelihood capital, coping behavior, and livelihood resilience among rice farmers. A quantitative approach using SEM-PLS was applied, involving 72 rice farmers as respondents. The findings indicate that the Sibedas Farmer Card policy does not significantly influence livelihood capital (β = -0.168, P = 0.135). However, livelihood capital has a significant effect on coping behavior (β = 0.713, P = 0.000) and livelihood resilience (β = 0.346, P = 0.012). Additionally, coping behavior significantly impacts livelihood resilience (β = 0.536, P = 0.000). These results suggest that strengthening livelihood capital enhances farmers' adaptability and resilience. While the program has been implemented, its effectiveness in improving farmers' livelihood capital remains limited. To optimize its impact, policymakers should expand farmers' access to training, technology, and financial support. Therefore, well-directed agricultural policies are essential to enhancing the sustainability of the agricultural sector in Bandung Regency. Keywords: maksimal 5 kata kunci, dan dipisahkan dengan tanda koma